Finance and Development, September 1977. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1977)
This paper highlights that since its inception in 1956, the International Finance Corporation (IFC) has invested more than USD 1.7 billion in nearly 300 enterprises in 62 developing countries in total projects costing about USD 9 billion. The IFC is the affiliate of the World Bank, which has been given the specific task of furthering economic development by encouraging the growth of productive private enterprise in developing countries. The paper underscores that IFC plays an essentially catalytic role in generating investment funds from local and foreign sources.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet